FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN: STUDI LITERATURE - Ernawati, Yohana; Ardini, Lilis (STIE PGRI Dewantara Jombang, 2023)
Indonesia's economic growth and development situation has a very immediate impact on competition. Competition has become tighter felt by various companies, namely trading companies, service companies, and manufacturing companies which have the same goal, namely to earn and increase profits by considering the existing market share to maintain viability. The research was conducted to determine the factors significantly affecting the acceptance of a going concern audit opinion. The factors influencing the receipt of a going concern audit opinion include the reputation of the Public Accounting Firm, company size, and the previous year's audit opinion. The research method used is a qualitative descriptive method in the form of a literature review/study of the literature; that is, the research results are explained in one sentence. The analysis results show that financial factors have a more significant influence in obtaining acceptance of a going concern audit opinion.